Pengaruh FoMO, Social Influence dan Product Involvement terhadap Purchase Decision Produk Iphone di Kota Semarang - Eko Prasetiyo; Imam Nuryanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the influence of FoMO, Social Influence and Product Involvement on Purchase Decision of iPhone products in Semarang City. This research is quantitative and involves a population of iPhone users with usage time > 3 months. The study uses a survey method by collecting data from respondents who meet the criteria of the research sample, using purposive sampling technique with a total of 100 respondents. Data were analyzed using multiple regression analysis technique through SPSS software version 25. The results of this study partially indicate that FoMO and Product Involvement have a significant positive effect on Purchase Decision, while Social Influence does not have a significant effect on Purchase Decision. The implications of these findings provide valuable insights for companies in designing more effective marketing strategies to increase sales of iPhone products.